2018
DOI: 10.1590/1980-5373-mr-2017-0973
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electroless Bath Parameters and Heat Treatment on the Properties of Ni-P and Ni-P-Cu Composite Coatings

Abstract: NiP -(Cu) composite coatings were applied on a St37 steel in an acidic bath of hypophosphite composite. The effect of the concentration of the Cu particles and pH of the solutionon the amount of Ni and P of the coatings, their morphology, and hardness of the coatings were explored. Some of the coated samples were also heat treated at 400ºC for 1 hour. The phases formed, the microstructure and the amount of the alloying elements of the coatings were analyzed by X-Ray powder diffraction (XRD), Scanning Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Due to the nature of their chemical bonding, ceramic compounds have stronger bonds than metals and as the result have higher resistance to indentation. [26][27][28][29][30][31] However, it can be clearly seen in substantially increased with increasing the temperature of the substrate during the HFCVD process. As observed in the XRD results, increasing the temperature of the substrate leads to the formation of WC, W 2 C compounds.…”
Section: Microstructural Observations and Phase Analysismentioning
confidence: 99%
“…Due to the nature of their chemical bonding, ceramic compounds have stronger bonds than metals and as the result have higher resistance to indentation. [26][27][28][29][30][31] However, it can be clearly seen in substantially increased with increasing the temperature of the substrate during the HFCVD process. As observed in the XRD results, increasing the temperature of the substrate leads to the formation of WC, W 2 C compounds.…”
Section: Microstructural Observations and Phase Analysismentioning
confidence: 99%
“…The amount of B for a specific material is obtained using the cathodic Tafel slope (b c ) and anodic Tafel slope (b a ) by the use of equation B= b c b a / 2.303(b c +b a ). [27][28][29] It can be observed from Table 4 that the slopes of Tafel anodic and cathodic zones for all four silver oxide electrodes are almost the same which shows similar anodic and cathodic reactions in corrosion mechanism of such electrodes. Also, the considerable point in Table 4 is the order of positioning the corrosion potentials and polarization resistance for all four silver oxide electrodes, which is in good accordance with open cycle potential tests versus the time as per Figure 6.…”
Section: Electrochemical Behavior Of Silver Oxide Electrodesmentioning
confidence: 68%
“…As a matter of fact, the Nyquist plots of electrochemical impedance spectroscopy test also show the decrease in the polarization resistance of silver oxide electrodes due to the increase in the carbon amount in silver oxide electrodes. From electrochemical impedance spectroscopy test, the real amounts of impedance resistance are 146 O.cm 2 for electrode A, 119 O.cm 2 for electrode B, 74 O.cm 2 for electrode C, and 42 O.cm 2 for electrode D. To sum up, comparing Nyquist plots of all four electrodes, it can be observed that the diameter of semi-circle in Nyquist plots, which is a symbol of polarization resistance of electrodes, [27][28][29] for the silver oxide electrode with 5wt% carbon (electrode A) is higher. Also, the results of corrosion resistance obtained from electrochemical impedance spectroscopy are in accordance with the results of polarization resistance obtained from potentiodynamic polarization test.…”
Section: Electrochemical Behavior Of Silver Oxide Electrodesmentioning
confidence: 97%
“…The hardness properties play an important role for coatings [48]. Thus, hardness was measured performing at least three different indentations, as shown in Figure 9.…”
Section: Vickers Hardness Testmentioning
confidence: 99%